The Effect of Interest in Utilisation of Information Technology on Indonesian Language Learning Outcomes of Class VIII Students of SMP Negeri 1 Gumelar - Hanifah, Dwiana Nur Rizki; Mukhibun, Akhmad; Ajengpitaloka, Ashanti Dayani; Sumarwati, Sumarwati (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2024)
As time progresses, technology has become something that is no longer foreign to the world of education. Most students and teachers have utilized technology for education. This research aims to examine differences in students' interest in using technology, both students with high and low interest in using technology, on the Indonesian language learning outcomes of class VIII students at SMP Negeri 1 Gumelar. especially in its use with students. The role of technology in the world. This research uses ex-post facto quantitative methods. The sampling technique in this research uses cluster random sampling and simple random sampling using lottery. Data collection techniques use document analysis of learning outcomes and technology use questionnaires. Based on the results of hypothesis testing using the t-test, students with a high interest in using technology have different Indonesian language learning outcomes from students who have a low interest in using technology. Based on the results of the average comparison, students with high interest in using technology have better Indonesian language learning outcomes than students with low interest in using technology. The results of the size effect test show that the influence of interest in using technology on students' Indonesian language learning outcomes is categorized as small. This is influenced by other variables not examined in this research.